Epidemiological Insights into Brucella Abortus Infection in Kundhi Buffaloes of Sindh Pakistan - Laghari, Riaz Ahmed; Khatri, Pershotam; Memon, Akeel Ahmed; Abro, Shahid Hussain (Indus Journal of Bioscience Research, 2025)
This study examines various factors contributing to Brucella abortus infection in Kundhi buffaloes in Sindh, Pakistan. Key objectives include assessing prevalence and risk factors linked to animal (age, sex, breeding), farm (size, type), and management practices (mating methods, vaccination, animal movements). Factors analyzed include age, sex, breeding status, vaccination, farm size/type, animal movements, contact with infected animals, and management practices like mating methods and range status. Staff at 30 Sindh farms participated in a cross-sectional research by providing data samples from 150 Kundhi buffaloes. A multivariate logistic regression model was used to discover the key risk elements that lead to Brucella abortus serological results in animals. Brucella abortus infection risk factors were identified as animal movements (OR = 3.7, 95% CI: 1.4–9.8), contact with infected animals (OR = 4.5, 95% CI: 1.8–11.3) and lack of vaccination (OR = 2.9, 95% CI: 1.2–7.4). Natural breeding of buffaloes and mating with a borrowed bull led to increased infection risks (OR = 1.9, 95% CI: 1.1–3.5 and OR = 2.3, 95% CI: 1.2–4.5, respectively). Farms with more than 100 livestock (OR = 2.6, 95% CI: 1.3–5.3) and shielding animals (OR = 3.4, 95% CI: 1.7–6.9) presented a considerably elevated chance of infection. Brucella abortus infection in Kundhi buffaloes of Sindh develops due to animal migration and unvaccinated status combined with inadequate handling methods. The intervention strategy must concentrate efforts on these vulnerable areas.